2006
DOI: 10.1007/s10979-006-9008-1
|View full text |Cite
|
Sign up to set email alerts
|

Mugshot Exposure Effects: Retroactive Interference, Mugshot Commitment, Source Confusion, and Unconscious Transference.

Abstract: More than 25 years of research has accumulated concerning the possible biasing effects of mugshot exposure to eyewitnesses. Two separate metaanalyses were conducted on 32 independent tests of the hypothesis that prior mugshot exposure decreases witness accuracy at a subsequent lineup. Mugshot exposure both significantly decreased proportion correct and increased the false alarm rate, the effect being greater on false alarms. A mugshot commitment effect, arising from the identification of someone in a mugshot, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
4
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 27 publications
5
140
4
1
Order By: Relevance
“…In culprit-absent conditions, 16% changed their decisions to make an innocent suspect selection. Similar carryover effects have been found in previous research (e.g., Deffenbacher et al, 2006;Dysart et al, 2001;Haw et al, 2007;Memon et al, 2002). In real cases, a person identified in a showup is likely to be arrested.…”
Section: Repeated Identification Proceduressupporting
confidence: 86%
“…In culprit-absent conditions, 16% changed their decisions to make an innocent suspect selection. Similar carryover effects have been found in previous research (e.g., Deffenbacher et al, 2006;Dysart et al, 2001;Haw et al, 2007;Memon et al, 2002). In real cases, a person identified in a showup is likely to be arrested.…”
Section: Repeated Identification Proceduressupporting
confidence: 86%
“…This suggests that people are less likely to remember the circumstances in which they encountered an individual of a different race. Research into bystander misidentification (Read et al, 1990;Ross et al, 1994) and mugshot exposure (Deffenbacher et al, 2006;Dysart et al, 2001) has shown that people can and do make mistakes concerning the context in which a face has been encountered. This study shows that these transference errors may be more likely in cross-race identifications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, participants may be unable to accurately remember whether a target individual was an assailant or a bystander at a crime (Read et al, 1990;Ross, Ceci, Dunning, & Toglia, 1994), or may be unable to recall whether an individual was seen at a crime scene or later, in a photo array (Deffenbacher, Bornstein, & Penrod, 2006;Dysart, Lindsay, Hammond, & Dupuis, 2001).…”
mentioning
confidence: 99%
“…First, when performing an identification test the witness must differentiate between feelings of recognizing a particular photo or lineup member as the culprit that arise from memories of that person perpetrating the crime versus from other sources (e.g., the similarity of a few superficial features of the suspect to the perpetrator, or memories of having seen the suspect in a prior lineup or in some other setting). Such source confusions are well-documented (e.g., Deffenbacher, Bernstein, & Penrod, 2006). Second, one person's perception of another person's performance on a memory test can be described as a sort of interpersonal metamemory or interpersonal source monitoring (e.g., Johnson, Bush, & Mitchell, 1998).…”
Section: Eyewitnesses' Suspect-identification Decisionsmentioning
confidence: 99%